Scarcity effect on impulse buying: The mediating role of arousal - Grace Angelica Suwito; MG Westri Kekalih Susilowati (Jurnal Fokus Manajemen Bisnis, 2025)
E-commerce, especially in Southeast Asia, is experiencing rapid growth, and flash sales are a powerful way to boost online shopping. They use scarcity (limited time or quantity) to create impulse buying. This research investigates the scarcity effect on online impulse buying through arousal as the mediating variable in e-commerce. This study was conducted on those who have experience shopping online through various e-commerce platforms. Using convenience sampling techniques, this study covered 225 respondents. Data was collected from October to November 2024 using an online questionnaire, namely Google form, WhatsApp private groups, and anWhatsAppram direct message distributed. This study used a quantitative analysis approach to achieve its objectives. The inferential analysis technique examines the nature of the hypothesized relationships between variables. Data is processed and analyzed by 2-stage regression through IBM SPSS Statistics 23. Meanwhile, the mediating variables were tested using the Sobel test and Daniel Sober Calculator. This study found that Limited-Time Scarcity significantly impacts arousal, but Limited-Quantity scarcity does not. Interestingly, only arousal had a significant direct impact on Impulse Buying, not the Scarcity factors. Additionally, the study revealed that arousal partially mediates limited-time Scarcity on Impulse Buying, but it doesn't mediate limited-quantity scarcity on Impulse Buying. This findings limitation is that the respondent's domicile is mainly in Semarang. Therefore, future research should explore other Indonesian cities. This findings implications is that e-commerce must focus on the limited time for their promotion events to arouse customers so that they can impulsively buy.